ALDH2 variance in disease and populations - Che-Hong Chen; Benjamin R. Kraemer; Daria Mochly-Rosen (The Company of Biologists, 2022)
The ALDH2*2 missense variant that commonly causes alcohol flushing reactions is the single genetic polymorphism associated with the largest number of traits in humans. The dysfunctional ALDH2 variant affects nearly 8% of the world population and is highly concentrated among East Asians. Carriers of the ALDH2*2 variant commonly present alterations in a number of blood biomarkers, clinical measurements, biometrics, drug prescriptions, dietary habits and lifestyle behaviors, and they are also more susceptible to aldehyde-associated diseases, such as cancer and cardiovascular disease. However, the interaction between alcohol and ALDH2-related pathology is not clearly delineated. Furthermore, genetic evidence indicates that the ALDH2*2 variant has been favorably selected for in the past 2000-3000 years. It is therefore necessary to consider the disease risk and mechanism associated with ALDH2 deficiency, and to understand the possible beneficial or protective effect conferred by ALDH2 deficiency and whether the pleiotropic effects of ALDH2 variance are all mediated by alcohol use.